2018
DOI: 10.5194/acp-18-1457-2018
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the ability to derive rates of polar middle-atmospheric descent using trace gas measurements from remote sensors

Abstract: Abstract. We investigate the reliability of using trace gas measurements from remote sensing instruments to infer polar atmospheric descent rates during winter within 46-86 km altitude. Using output from the Specified Dynamics Whole Atmosphere Community Climate Model (SD-WACCM) between 2008 and 2014, tendencies of carbon monoxide (CO) volume mixing ratios (VMRs) are used to assess a common assumption of dominant vertical advection of tracers during polar winter. The results show that dynamical processes other … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 81 publications
(83 reference statements)
3
24
0
Order By: Relevance
“…2a). Our velocity estimates are similar to those of Salmi et al (2011), who found that mesospheric NO x anomalies during the major SSW of 2009 were transported from 80 to 55 km in about 40 d, i.e., with a velocity of −600 m d −1 .…”
Section: Northern Hemisphere Ssw Effectssupporting
confidence: 89%
See 1 more Smart Citation
“…2a). Our velocity estimates are similar to those of Salmi et al (2011), who found that mesospheric NO x anomalies during the major SSW of 2009 were transported from 80 to 55 km in about 40 d, i.e., with a velocity of −600 m d −1 .…”
Section: Northern Hemisphere Ssw Effectssupporting
confidence: 89%
“…Mesospheric responses to the SSW are observed as enhancement in planetary wave amplitude, zonal wind reversal, and significant air cooling (Shepherd et al, 2014;Zülicke and Becker, 2013;Stray et al, 2015;Zülicke et al, 2018); substantial depletion of the metal layers (Feng et al, 2017;Gardner, 2018); and mesosphere-to-stratosphere descent of trace species (Manney et al, 2009;Salmi et al, 2011). The SSW events are also accompanied by the rapid descent of the stratopause into the stratosphere at the SSW onset, followed by formation of the elevated stratopause in the lower mesosphere and gradual stratopause lowering toward its typical position in the SSW recovery phase (Manney et al, 2009;Chandran et al, 2011;Salmi et al, 2011;Tomikawa et al, 2012;Limpasuvan et al, 2016;Orsolini et al, 2010Orsolini et al, , 2017. The elevated stratopause events provide evidence for the coupling between the stratosphere and the mesosphere.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that the BDC terms related to the North Pacific SSTAs play a key part in determining the changes in ozone concentration, but also that the eddy transport and chemical processes related to the SSTAs in the North Pacific may modulate the concentration of ozone. The residual term actually contains three terms that modify the ozone concentration: chemical production; molecular diffusion; and gravity waves (Ryan et al, ). Ryan et al () showed that the magnitudes of the gravity wave and molecular diffusion terms are smaller than the chemical processes term in the northern hemisphere.…”
Section: Possible Dynamic Mechanismsmentioning
confidence: 99%
“…The residual term actually contains three terms that modify the ozone concentration: chemical production; molecular diffusion; and gravity waves (Ryan et al, ). Ryan et al () showed that the magnitudes of the gravity wave and molecular diffusion terms are smaller than the chemical processes term in the northern hemisphere. The residual term in equation may be an approximation of the net chemical production term.…”
Section: Possible Dynamic Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation